(untitled) (REVISTA NODO, 2022)
This paper analyzes the reasons why much of contemporary art continues to be an experience not yet assimilated today, focusing on the study of the factors that potentially determine the aesthetic experience of the work of art of our time; it raises a reflection that relates areas of cultural, artistic and historical knowledge, with a view to offering a work that delves into the creative processes of contemporary art and the origin of detachment between contemporary and public art. The statements about the presence of romantic culture and the need for a new viewer can offer light to place us in the reality of the problem, and possibly the excess of aesthetic discourse is the cause of it, as well as the abandonment of the theory of proportion and harmony in the plastic and visual arts, and the renunciation of the idea of narration in musical art.